Physical Education Curriculum in Elementary Schools: Efforts for Sustainable Movement Education - Indarto, Pungki; Nasuka; Furqon Hidayatullah; Sulaiman; Heny setyawati (Universitas Negeri Semarang, 2025)
This study aims to gain new knowledge about sustainable movement education efforts in the elementary school curriculum. The method used is library research. This study uses secondary data collected through documentation methods. Data from various documents will be collected as literature, with a focus on research on the Physical Education Curriculum to support Sustainable Movement Education Efforts. Article searches were conducted through Google Scholar, GARUDA, and other high-achieving journals. The literature obtained must meet the Inclusion and Exclusion Criteria, and be in accordance with keywords such as Curriculum, Physical Education, Elementary School, Movement Education, and the Digitalization Era. The researcher selected 13 articles and journals on physical education that met the criteria and keywords set. The analysis method used is descriptive analysis. The conclusion of 13 works of literature on the physical education curriculum in elementary schools shows that the independent curriculum is more effective than the previous curriculum, with the support of technology and applications in learning that encourage the progress of physical education. Current movement education with an independent curriculum and innovative technology reflects sustainable movement education in elementary schools.